Investigating the effect of butanol isomers on combustion and emissions in port injection dual fuel diesel engines: an experimental study - Kilinc, Mehmet Ferruh; Ozturk, Gokhan; Firat, Mujdat (Public Library Science, 2025)
The present study examines the effects of substituting alternative fuels for diesel fuel and employing a dual fuel approach on diesel engine combustion characteristics and emissions. Various butanol isomers, namely & imath;so-butanol, n-butanol, tert-butanol, and sec-butanol, were chosen as novelty alternative fuels. In dual fuel combustion strategy, diesel fuel was injected directly into the cylinder, while butanol isomers as a secondary fuel were introduced into the cylinder at the beginning of the intake period using a port injection technique. The tests were repeated for 15%, 30%, and 45% premixing ratios (Rp) of butanol isomers. This study presents detailed combustion parameters and pollutant emission findings produced in diesel engines employing a dual fuel strategy with butanol isomers. In general, an increase within in cylinder pressure and heat release rate was observed. Especially at a premixing ratio of 45%, an increase of 50% within heat release rate was observed. Use of all butanol isomers increased the ignition delay and shortened combustion duration. Brake thermal efficiency remained at acceptable levels, and ringing intensity was below the knock limit. In addition to an increase in CO and HC emissions, NOX emissions were also up at other premixing ratios but declined at 15%. High levels of decreased smoke opacity were recorded. Especially at a premixing ratio of 45% iso-butanol, a decrease up to 90% is remarkable. In conclusion, the combustion characteristics and pollutant emission results obtained from the experimental engine are discussed in detail according to the operating parameters. The obtained findings provide important information about the performance and emission profiles of alternative fuels and dual fuel systems and provide guidance for future research.
Keywords: N-Butanol; Biodiesel; Gasoline; Reactivity; Methanol